Study of the content of chlorites in chlorine dioxide-treated Dniprovo drinking water and assessment of their danger to the health of water consumers (Environment & Health, 2024)
The purpose of the study: analysis of the content of chlorine dioxide and chlorites in drinking water, which enters the water supply networks of certain districts of Kyiv from the Dnipro water supply, and assessment of the non-carcinogenic risk from its consumption for the health of water consumers.Research materials and methods. An analysis of three-year (2021-2023) studies of the quality of drinking water, including the content of chlorites treated with chlorine dioxide, was performed. Which comes from the Dnipro water pipeline in Kyiv to the distribution networks of Podуlskyi, Svyatoshynskyi and Shevchenkуvskyi districts. Testing of tap water for chlorite content was carried out by the laboratory of «Kyivvodokanal» and the selective water laboratory of the Institute. Determination of chlorites was carried out on an ion chromatograph and titrimetric method according to Yu.Yu. Lurie. The non-carcinogenic health risk from drinking water with different levels of toxic chlorites was calculated according to the Guidelines of the International Agency for Research on Cancer (IARC). Research methods: statistical evaluation of factual and analytical material.The results. Research (2021-2023) has established that the use of chlorine dioxide instead of chlorine in concentrations 1,0-3,0 mg/l on the Dnipro water supply system in Kyiv in the traditional water treatment technology is accompanied by a decrease in the oxidant level and the formation of dangerous chlorites in drinking water, the number of which changes according to the seasons of the year. The content of chlorites in drinking water from the distribution networks of Podуlskуі, Svyatoshynskуі and Shevchenkуvskyі districts is a mirror image of their levels in water from the pure water tank of the Dnipro water supply system, which are subject to seasonal dose-time dependence. In winter, they are 0,17-0,39 mg/l, and in summer – 0,32-0,59 mg/l, which exceeds the national standard (0,2 mg/l), especially in summer from 1,5 up to 2,5-3 times. During the observation period, residual concentrations of chlorine dioxide in drinking water from networks were mostly within the standard (≤0,1 mg/l) or slightly exceeded it in individual samples. According to microbiological and sanitary-chemical indicators, the water met the sanitary requirements for tap water. In connection with the excess of chlorite content in drinking water for different levels from 0,2 mg/l (Ukrainian standard) to 0,7 mg/l (WHO standard), a non-carcinogenic risk to human health was calculated and assessed. It is shown that within these values of chlorites in drinking water, the hazard ratio (HQ) does not exceed 1,0, which characterizes it as permissible (acceptable), which does not pose a threat to human health.Conclusions. It is shown that the use of chlorine dioxide instead of chlorine in water treatment technology ensures the required quality of drinking water in terms of microbiological and sanitary-chemical indicators. But at the same time, dangerous chlorites are formed in it in concentrations ranging from normative to over-normative. A non-carcinogenic risk assessment for water levels of chlorites from 0,2 mg/l to 0,7 mg/l, according to the hazard ratio (HQ), showed that within these limits, chlorites in water do not pose a threat to human health. We raise a question before the Ministry of Health of Ukraine about the feasibility of changing the national standard for chlorites in drinking water from 0,2 mg/l to 0,7 mg/l.
Keywords: drinking water; water treatment; water distribution networks; chlorine dioxide; chlorites; non-carcinogenic risk